Diagnostic yield, safety, and impact of transbronchial lung biopsy in mechanically ventilated, critically ill patients: a retrospective study - Ghiani, Alessandro (BMC Pulm Med, 2021)
BACKGROUND: Pulmonary infiltrates of variable etiology are one of the main reasons for hypoxemic respiratory failure leading to invasive mechanical ventilation. If pulmonary infiltrates remain unexplained or progress despite treatment, the histopathological result of a lung biopsy could have significant impact on change in therapy. Surgical lung biopsy is the commonly used technique, but due to its considerable morbidity and mortality, less invasive bronchoscopic transbronchial lung biopsy (TBLB) may be a valuable alternative. METHODS: Retrospective, monocentric, observational study in mechanically ventilated, critically ill patients, subjected to TBLB due to unexplained pulmonary infiltrates in the period January 2014 to July 2019. Patients’ medical records were reviewed to obtain data on baseline clinical characteristics, modality and adverse events (AE) of the TBLB, and impact of the histopathological results on treatment decisions. A multivariable binary logistic regression analysis was performed to identify predictors of AE and hospital mortality, and survival curves were generated using the Kaplan-Meier method. RESULTS: Forty-two patients with in total 42 TBLB procedures after a median of 12 days of mechanical ventilation were analyzed, of which 16.7% were immunosuppressed, but there was no patient with prior lung transplantation. Diagnostic yield of TBLB was 88.1%, with AE occurring in 11.9% (most common pneumothorax and minor bleeding). 92.9% of the procedures were performed as a forceps biopsy, with organizing pneumonia (OP) as the most common histological diagnosis (54.8%). Variables independently associated with hospital mortality were age (odds ratio 1.070, 95%CI 1.006–1.138; p = 0.031) and the presence of OP (0.182, [0.036–0.926]; p = 0.040), the latter being confirmed in the survival analysis (log-rank p = 0.040). In contrast, a change in therapy based on histopathology alone occurred in 40.5%, and there was no evidence of improved survival in those patients. CONCLUSIONS: Transbronchial lung biopsy remains a valuable alternative to surgical lung biopsy in mechanically ventilated critically ill patients. However, the high diagnostic yield must be weighed against potential adverse events and limited consequence of the histopathological result regarding treatment decisions in such patients.